Effectiveness of XP‐endo Finisher and XP‐endo Finisher R in removing root filling remnants: a micro‐CT study. (29th May 2017) - Silva, E. J. N. L.; Belladonna, F. G.; Zuolo, A. S.; Rodrigues, E.; Ehrhardt, I. C.; Souza, E. M.; De‐Deus, G.
Abstract: Aim: To evaluate the efficacy of filling material removal from oval‐shaped canals after the use of supplementary files (XP‐endo Finisher and XP‐endo Finisher R) through microcomputed tomographic (micro‐CT) analysis. Methodology: The root canals of twenty maxillary single‐rooted teeth were prepared with Reciproc R25 files and filled with gutta‐percha and AH Plus sealer using the continuous wave of condensation technique. The root canals were then retreated using Reciproc R25 and R40 instruments. After this, the specimens were assigned to two groups according to the supplementary cleaning approach, using XP‐endo Finisher and XP‐endo Finisher R. The surface area and volume of removed filling material was assessed using micro‐CT imaging before and after the use of the XP‐endo instruments. Data were analysed statistically with a significance level of 5%. Results: Removal of filling material at 66.8% and 59.4% in volume and 67.3% and 61.4% in surface area was seen for the XP‐endo Finisher and the XP‐endo Finisher R files, respectively. The amount of filling material removed by both supplementary files was highly significant ( P  = 0.000). No significant difference in the percentage of removed filling material was detected for the XP‐endo instruments ( P  = 0.636 for volume and P  = 0.667 for surface area). Conclusions: Both XP‐endo files were equally effective in the removal of remaining filling material from straight oval‐shaped canals. None of the instruments were able to remove all the residual filling material.